Um cenário de educação linguística crítica, integral e humanizadora na infância com texturas da Pedagogia Waldorf - Lorenzoni, Carla Raqueli Navas (2022)
This research is related to the experiences (DEWEY, 1979) of additional language teachers in the initial years of schools that follow the Waldorf Pedagogy (STEINER, 1995, 2003, 2015 among others), which is based on a broad and complete view of the human being and his development; from this point of view, children and young people are considered in their individual aspects and in the particularities of the age group to which they belong. The theoretical contribution of this thesis is anchored in the definitions of critical linguistic education (MONTE MÓR, et al., 2018; SABOTA, 2021; FERRAZ, 2015, 2018, 2019), integral education, humanizing education (MORIN, 2017; MOLL, 2019; GUERRA, 2019; GUARÁ, 2006) and transdisciplinar education (LEFFA, 2006; MORIN, 2017) and Waldorf Pedagogy (STEINER, 1995, 2003, 2015; KÜGELGEN, 1984; KIERSCH, 2015; SELG, 2020). The general objective of the research is to report and critically interpret the proposal for language education in Waldorf Pedagogy based on experiences shared by additional language teachers working in schools that follow this pedagogy. The specific objectives are: 1. to investigate and evaluate possible developments of aspects of critical linguistic education and the panorama of additional languages in Waldorf Pedagogy that complement each other and 2. to identify aspects conducive to the critical, integral and humanizing formation of the student in additional language classes from the experiences shared by the teachers/participants. The research methodology that guides the study is the Narrative Research (CLANDININ and CONNELLY, 2011; MELLO, 2004), which directed being in the field, the composition of meanings from field texts and also the emergence of research texts. There were two teachers/participants who shared their experiences of working in the classroom. From these experiences, themes such as transdisciplinarity, ludicity, learning assessment, the integral formation of the student and the humanization of education emerged. With the discussions made from the research texts, it is noted that there is, in additional language classes of Waldorf Pedagogy, the experience of critical linguistic education: the performance of the teachers/participants denotes a work based on the construction of meanings, on the contextualization, respect for the affective character of being, lovingness, dialogue with students. Such action excels in student’s critical, comprehensive and humanizing education.